Thermal performance enhancement and optimization of two-phase closed thermosyphon with graphene-nanoplatelets coatings. (15th May 2021) - Ng, Ving Onn; Yu, Hao; Wu, Heng An; Hung, Yew Mun
Highlights: We integrate graphene nanoplatelets coatings into TPCTs for enhanced performance. Superhydrophilic graphene profoundly enhances the evaporation and circulation rates. Hydrophobic graphene coating augments the condensation rate at the condenser. Evaluation of optimized length ratio enables optimum design of TPCT's dimensions. Molecular dynamics simulations justify the ultrafast water transport in graphene. Abstract: The enhancement of phase-change heat transfer in the two-phase closed thermosyphon (TPCT) coated with graphene-nanoplatelets (GNPs) of different wettability is investigated. The intrinsically hydrophobic GNPs can be modified to become superhydrophilic through a simple thermal curing process. The performance of a TPCT is governed by three major processes, namely evaporation, condensation and circulation of condensate. By benchmarking with the uncoated TPCT, we experimentally examine the thermal enhancement and comprehend the thermal characteristics of the GNPs-coated TPCTs with different wettability. Endowed with the unique rapid water permeation property, the superhydrophilic graphene nanocapillaries spread the water film to a larger surface area which is favourable to the evaporation; a maximum enhancement of 96.2% is achieved by employing the Jakob number as an indicator. The uncured hydrophobic GNPs-coating is well suited to the condensation process that leads to an enhancement of 20.6%. By evaluating the minima of the total thermal resistance of the TPCT, the thermal optimization can be achieved by determining the optimized length ratio of the evaporator length to the condenser length. Computationally, molecular dynamic simulations are performed to provide insights on the rapid water permeation process that leads to the filmwise evaporation in the cured superhydrophilic GNPs-coating. This study is particularly of great interest for the potential applications of the graphene functionalized coatings in the field of phase-change heat transfer.